Gonadal function in patients with 47,XYY syndrome: a systematic review and meta-analysis - Rossella Cannarella; Andrea Pedano; Michele Compagnone; Sandro La Vignera; Rosita A Condorelli; Aldo E Calogero (Endocrine Connections)
The 47,XYY syndrome, or Jacobs syndrome, is a chromosomal disorder affecting approximately one in 1000 male births. While often asymptomatic or mildly expressed, it is associated with various physical, cognitive and behavioral features. Early studies erroneously linked the condition to aggressive behavior and elevated testosterone levels, largely based on incarcerated populations. Recent evidence contradicts this, showing testosterone levels in 47,XYY individuals are typically normal or lower than in 46,XY males. This systematic review and meta-analysis of 362 patients examine hormonal, testicular and fertility outcomes in 47,XYY syndrome. Findings reveal significantly lower testosterone levels and elevated luteinizing hormone and follicle-stimulating hormone, indicating impaired gonadal function. While testicular volumes are often normal, many patients exhibit reduced size and a notable proportion experience oligozoospermia or azoospermia. These outcomes highlight the need for counseling regarding infertility and hormonal imbalances. This review dispels the myth of 47,XYY as a ‘super-male syndrome’, emphasizing the complexity of hormonal, testicular and psychological factors. It underscores the importance of early diagnosis and a multidisciplinary approach to address endocrine and reproductive health. Regular monitoring for hypogonadism and consideration of assisted reproductive technologies are recommended to support affected individuals.